Not Guilty? : Another Look at the Nature and Nurture of Economics Students - Justus Haucap; Tobias Just (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
In this paper, we examine students' attitudes towards various allocation mechanisms for a scarce resource. For this purpose, we have run a survey among officers of the German military who are enrolled in different courses of study (such as economics) at the University of the German Federal Armed Forces. We find that significantly more economics than non-economics students judge price increases as fair. Moreover, this tendency strengthens as economics students advance in their studies. In addition, fewer advanced economics students judge allocation through the local community as fair when compared to first-year economists or other students. These results stand in contrast to results obtained by Frey, Pommerehne and Gygi (1993) on the same survey. In summary, we find evidence for both nature and nurture effects.
urn:nbn:de:gbv:705-opus-1366
Keywords: D63; A12; A20; A13; 330; Economists; fairness; learning; selection; attitudes; Wirtschaftswissenschaftler; Meinung; Gerechtigkeit; Marktmechanismus; Allokation; Schätzung; Deutschland